2017
DOI: 10.1142/s1793545817500109
|View full text |Cite
|
Sign up to set email alerts
|

Association between central obesity and executive function as assessed by stroop task performance: A functional near-infrared spectroscopy study

Abstract: Recent studies have suggested a link between executive function (EF) and obesity. Studies often adopt body mass index (BMI), which re°ects the distribution of subcutaneous fat, as the sole marker of obesity; however, BMI is inappropriate to distinguish central obesity, which indicates the centralized distribution of visceral fat. Visceral fat compared with subcutaneous fat represents greater relative lipid turnover and may increase the risk of cognitive decline in older adults. However, the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…As hypothesised, we found a reduction in PFC signalling across the OB phenotypes compared to individuals with NW. This is in line with previous fNIRS [ 36 , 37 ] and fMRI research [ 22 , 25 ] highlighting the PFC’s role in dietary self-regulation. Yet, the causal pathways for this well-established association between PFC perturbations and OB development are far from understood [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As hypothesised, we found a reduction in PFC signalling across the OB phenotypes compared to individuals with NW. This is in line with previous fNIRS [ 36 , 37 ] and fMRI research [ 22 , 25 ] highlighting the PFC’s role in dietary self-regulation. Yet, the causal pathways for this well-established association between PFC perturbations and OB development are far from understood [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although fNIRS has enormous potential in psychiatry research [35], it has rarely been used to study OB and eating disorders [33]. The only available study using fNIRS in individuals with OB found a decreased hemodynamic response relative to individuals with overweight (BMI ≥ 25 kg/m 2 ) in the left frontopolar area and bilateral DLPFC during a Stroop task [36]; however, no NW group has been included. Although there is no study using fNIRS in BED available, Suda et al (2010) reported a negative correlation between fNIRS-based left OFC activity and binge-eating scores in a sample of individuals with various eating disorders [37].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have provided behavioral and neurological evidence that overweight people have poorer cognitive flexibility [3,9], and the effect was confirmed by different paradigms [10,11]. Neurological evidence for overweight individuals in switching tasks suggests that cognitive flexibility is associated with the activation of the dorsolateral prefrontal cortex, ventrolateral prefrontal cortex, inferior frontal gyrus, superior temporal gyrus, auxiliary motor areas, and parietal gyrus [12][13][14][15][16]. The neural mechanisms of cognitive flexibility that are affected by overweight include high-level executive control brain regions and the perception and emotional processing cortex.…”
Section: Introductionmentioning
confidence: 85%
“…[44][45][46][47] Recent studies have also identified functional and neuroanatomical differences in the dlPFC of individuals with obesity compared to healthy controls. [48][49][50] While this evidence could suggest that executive function is mediating the relationship between dlPFC function and obesity, others have suggested that the causal direction is bidirectional, [51,52] or even reversed (i.e. with obesity causing impaired executive function).…”
Section: Chapter 13 -Executive Function and Obesitymentioning
confidence: 99%